Foundation Provision - a Social Justice Perspective - Leibowitz, Brenda; Bozalek, Vivienne (South African Journal of Higher Education, 2016)
The article uses data gathered during monitoring and evaluation work at two institutions, policy documents, published articles, correspondence with key role-players at South African higher education institutions and other documents in the public domain in order to present a critique of the existing foundation provision and policy. We argue that foundation provision focuses on a narrow band of students, over a limited time period and that it separates the educational thinking and planning for the foundation students from the mainstream. This is to the detriment of either group of students and lecturers. We suggest questions for further investigation regarding foundation provision, based on the throughput trends across the country and institutional reports, which would shed light on the effectiveness of the present approach. We share two approaches which we believe offer productive alternative ways of thinking about the curriculum and arrangements for learning, for the benefit of all students and lecturers, namely Universal Design for Learning and a Capabilities Approach.